Associations of handgrip weakness and asymmetry with new-onset stroke in Chinese middle-aged and older adults: a cohort study - Zhang, Yuying; Chen, Weiqing; Cao, Bing; Lin, Li; Li, Jinghua; Guo, Vivian Yawei (Frontiers in Public Health, 2023)
Background: Weak handgrip strength (HGS) has been linked to adverse health outcomes including stroke. However, the joint associations of HGS weakness and asymmetry between limbs with stroke incidence remain underexplored. Methods: This cohort study analyzed data of participants aged ≥45 years from three waves (2011, 2013, and 2015) of the China Health and Retirement Longitudinal Study. Weak HGS was defined according to the recommendation of European Working Group on Sarcopenia in Older People. Asymmetric HGS was defined if the HGS ratio of both hands was over 1.1 or below 0.9. New-onset stroke was confirmed through self-report of physician's diagnosis. Results: A total of 10,966 participants without stroke at baseline were included in the analysis. During the 4-year follow-up, there were 262 (2.39%) new-onset stroke cases. Compared to individuals with non-weak and symmetric HGS, those with HGS asymmetry alone and weakness alone were associated with hazards of 1.10 09 (95% confidence interval [CI]: 0.80-1.4948) and 1.28 27 (95%CI: 0.8786-1.9088) for new-onset stroke, respectively, while cooccurrence of both HGS asymmetry and weakness was associated with 1.83 80 (95%CI: 1.2624-2.6460) greater hazard for new-onset stroke after controlling for confounders. Such associations were consistent in older adults aged ≥60 years, but not in those aged<60 years. Conclusions: Individuals with both weak and asymmetric HGS tended to have greater risk of new-onset stroke, compared to those with normal HGS, or with either weak or asymmetric HGS alone. Our finding suggested that examining HGS asymmetry alongside weakness may help to improve the riskstratification and target prevention of stroke, particularly in the elderly population.